Shelf Life Prediction and Isotherm Sorption Model of Dried Grain and Powdered Black Pepper (Piper ningrum L.) - Winiati P Rahayu; M Arpah; Erika Diah (Jurnal Teknologi dan Industri Pangan, 2005)
Black pepper is one of the most popular spice traded around the globe, either in dried grain form or in bulky powder. However, for retailing purpose both are usually packaged in plastic film. This research was conducted to predict the shelf life of packaged black pepper (both dried grain and powder) by applying isotherm sorption and Labuza models. Initial moisture content of dried grain was 12.17 % d.b and for the powder was 10.27 % d.b. The shelf life of black pepper calculated for the dried grain was longer than the powder. When stored at 90 % RH, the dried grain black pepper packaged in HDPE demonstrated the longest shelf life which was equal to 2187 days and for the powder equal to 2037 days. The volatile oil loss for dried grain black pepper after 30 days of preservation was 1.36 % and for the powder was 40.82 %. Key words: Black pepper, shelf life, plastic film.